A Review of the Conceptual Structure and Evolution of Digital Leadership Research in Education - Karakose, Turgut; Polat, Hakan; Tulubas, Tijen; Demirkol, Murat (Mdpi, 2024)
With the advent of digital technologies that have rapidly changed the functioning of societies, digital leadership has also become a novel imperative for the effective functioning of organizations. As the backbone of societal development, educational institutions have not been exempt from the influence of these new trends, which has ignited a growing research interest in the digital leadership roles of school administrators. This study aims to map the conceptual and thematic evolution of this research on digital leadership in the education field to offer a better insight into the strategic themes that are sufficiently or insufficiently addressed; that is, to identify aspects that are clearly defined or left shrouded in shadow. This study employed science mapping methodology and used SciMAT software (version 1.1.04) to map the evolution of thematic strands across three periods of the field's development. The analysis was conducted using metadata obtained from 174 articles that are indexed on WoS and Scopus. The results indicated that with a growing focus on technology or e-leadership, considering the developments in the world of computers and the internet, research into digital leadership has gained momentum in recent years, particularly following the COVID-19 pandemic. Digital leadership is regarded as a broader concept for application in investigating the knowledge, skills, competencies, and perspectives of school leaders to facilitate the healthy integration of digital technologies into education, school administration, and student learning. The field seems to require investigations into the many aspects of digitalization in education to build a more solid and insightful knowledge base to guide the effective practice of digital leadership in schools.
Keywords: digital leadership; school administration; school leadership; science mapping; education; SciMAT